Share Price Model in Lq45 Companies Listed on The Indonesia Stock Exchange - Dwi Sihono Raharjo (Dinasti International Journal of Education Management And Social Science, 2023)
This research undertakes an in-depth analysis to examine the correlation between Price to Book Value, Price Earning Ratio, and asset growth on stock prices. Return On Equity was used as a moderating variable in scrutinizing LQ45 companies registered on the Indonesia Stock Exchange. The study targeted companies featured in the LQ45 list on the Indonesia Stock Exchange during 2019 - 2022. A purposive sampling method was employed to select a representative sample of 26 companies for the regression analysis, which was conducted using a multiple linear model. The results indicated that Price to Book Value, Price Earning Ratio, and asset growth collectively had a significant impact on stock prices. However, individually, Price to Book Value and asset growth demonstrated a notable effect on stock prices. Residual test analyses were also carried out to validate the results. The impact of the price earning ratio on stock prices is negligible. However, it's worth noting that the profitability variable can act as a moderating variable, either amplifying or diminishing the influence of independent variables on stock prices.